PENGARUH KOMPETENSI KARYAWAN, DUKUNGAN TOP MANAJEMEN, DAN PENDIDIKAN DAN PELATIHAN TERHADAP PEMANFAATAN SISTEM INFORMASI AKUNTANSI DALAM PELAPORAN PERPAJAKAN - Nunik Widiyaningsih, Siti Nurlaela & Endang Masitoh W (Universitas Slamet Riyadi, 2019)
This study aims to determine and analyze the influence of employee competence, top management support and education and training on the utilization of accounting information systems in tax reporting. Sampling method using purposive sampling method. Respondents sampled in this study amounted to 98 employees. Data analysis methods used in this research are: 1) instrument test (validity and reliability test), 2) classical assumption test (normality test, heteroscedasticity, multicollinearity, and autocorrelation), 3) multiple linear regression analysis (multiple linear regression model , model feasibility test (F test), hypothesis test analysis (t test), and coefficient of determination). The result of hypothesis analysis (t test) shows that the variables of employee competence, top management support and educating and training affect the utilization of accounting information system in tax reporting. Keyword: Employee Competence, Top Management Support, Education and Training, Utilization of Accounting Information System